Knowledge and behaviors about hepatitis B prevention and control among carriers of hepatitis B surface antigen - LI Siwen, ZHOU Tiantian, ZHANG Chao, ZHANG Dan, HU Weijun (预防医学)
Objective: To investigate the knowledge and behaviors related to hepatitis B prevention and control among carriers of hepatitis B surface antigen (HBsAg), so as to provide the basis for conducting health education and interventions for HBsAg carriers. Methods: Based on the seroepidemiological survey of hepatitis B among individuals aged 1 to 69 years in Shaanxi Province, HBsAg carriers were selected as the study subjects. Basic information, knowledge and behaviors about hepatitis B prevention and control were collected through questionnaire surveys. The awareness of hepatitis B prevention and control knowledge and related behaviors among HBsAg carriers were analyzed. Results: A total of 107 HBsAg carriers were enrolled, including 52 males (48.60%) and 55 females (51.40%), and had a median age of 47.04 (interquartile range, 19.78) years. The awareness of hepatitis B prevention and control knowledge ranged from 56.07% to 87.85% among HBsAg carriers, with the highest awareness for "hepatitis B vaccination can effectively prevent hepatitis B "(87.85%), and the lowest awareness for "sharing meals with HBsAg carriers or hepatitis B patients will not lead to infection" (56.07%) and "hepatitis B can be treated with antiviral drugs" (61.68%). The proportions of those who did not seek medical consultation, undergo regular check-ups, or receive treatment were relatively high, at 65.42%, 72.90% and 77.57%, respectively. Conclusions: The awareness of hepatitis B transmission routes and treatment-related knowledge among HBsAg carriers is relatively low, and their medical-seeking behaviors are relatively passive. There is a need to enhance the dissemination of hepatitis B prevention and control knowledge, improve medical-seeking behaviors, and reduce the risk of hepatitis B virus transmission.